Alternating polymers based on fluorinated alkoxyphenyl-substituted benzo[1, 2-b:4, 5-b′]dithiophene and isoindigo derivatives for polymer solar cells. (November 2017) - Cong, Zhiyuan; Liu, Hongli; Wang, Weiping; Liu, Jianqun; Zhao, Baofeng; Guo, Zhaoqi; Gao, Chao; An, Zhongwei
Abstract: To effectively modulate the molecular energy levels of isoindigo-based polymers through side-chain modification on the donor segments, three alkoxyphenyl-modified benzo[1, 2-b:4, 5-b′]dithiophene (BDT) were synthesized and used as electronic-donor units, which were copolymerized with the electron-withdrawing segment 2-ethylhexyl-substituted isoindigo (IID) to construct donor-acceptor (D-A) polymers. The obtained three polymers are named asP-IID, m F-IID and o F-IID, which possess 4-(2-octyldodecaneoxy)-phenyl, 2-fluoro-4-(2-octyldodecaneoxy)-phenyl and 3-fluoro-4-(2-octyldodecaneoxy)-phenyl side-chains in the BDT unit, respectively. All polymers display broad absorption regions with the film absorption edges of 759 nm (P-IID ), 742 nm ( m F-IID ) and 726 nm ( o F-IID ). The fluorination on the phenyl side-chains of BDT unit results in obvious blue-shift in the absorption spectra, especially for the ortho -position fluorinated polymer o F-IID because of the enlarged dihedral angles between the phenyl rings and the BDT backbones. Gradient reduction in the highest occupied molecular orbital (HOMO) energy levels are observed for the three polymers, with HOMO values of −5.35 eV forP-IID,  −5.48 eV for m F-IID and −5.53 eV for o F-IID, separately. As the result of the HOMO energy levels, polymer solar cells (PSCs) with inverted device configuration by blending the polymers with [6, 6]-phenyl-C71 butyric acid methyl ester (PC71 BM) show continually increased open circuit voltage ( V oc ) from 0.84 V forP-IID to 0.88 V ( m F-IID ) and then a notable value of 0.96 V for o F-IID . However, the fluorination leads to intensively reduced short-circuit current density ( J sc ) of the PSCs, 9.68 mA cm −2 forP-IID, 5.61 mA cm −2 for m F-IID and a very low value of 1.61 mA cm −2 for o F-IID, respectively. Consequently, moderate power conversion efficiency (PCE) of 5.23% is achieved for the non-fluorinated polymerP-IID as well as a decreased value of 2.50% for the meta -fluorinated polymer and a very low PCE of 0.93% for the ortho -fluorinated polymer. These results imply that although fluorine substituted side-chain in the donor unit can effectively deepen the HOMO energy levels of the polymers to obtain enlarged V oc, the absorption losses of the fluorinations caused low J sc should be taken into consideration to design high efficient electron-donating alternating polymers for polymer solar cells. Highlights: Three alternating polymers based on fluorinated alkoxy-phenyl modified BDT and isoindigo were synthesized. All polymers showed good thermal stabilities, finely tunable bandgaps and gradient adjusted energy levels. A moderate PCE of 5.23% was achieved for the non-fluorinated polymerP-IID blended with PC71 BM.